Size-Controllable Enzymatic Synthesis of Short Hairpin RNA Nanoparticles by Controlling the Rate of RNA Polymerization - Kim, Hyejin (Polymers (Basel), 2018)
Thanks to a wide range of biological functions of RNA, and advancements in nanotechnology, RNA nanotechnology has developed in multiple ways for RNA-based therapeutics. In particular, among RNA engineering techniques, enzymatic self-assembly of RNA structures has gained great attention for its high packing density of RNA, with a low cost and one-pot synthetic process. However, manipulation of the overall size of particles, especially a reduction in size, has not been studied in depth. Here, we reported the enzymatic self-assembly of short hairpin RNA particles for the downregulation of target genes, and a rational approach to the manipulation of the resultant particle size. This is the first report of the size-controllable enzymatic self-assembly of short hairpin RNA nanoparticles. While keeping all the benefits of an enzymatic approach, the overall size of the RNA particles was controlled on a scale of 2 μm to 100 nm, falling within the therapeutically applicable size range.